Ketidakhadiran Pemimpin Perempuan di Forum Komunikasi Mahasiswa Bojonegoro Universitas Negeri Surabaya dalam Persepsi Pengurus dan Anggota - Charisa Candra Selvia; Oksiana Jatiningsih (Kajian Moral dan Kewarganegaraan, 2023)
FKMB Unesa is a Regional Student Organization from Bojonegoro at Unesa. Since its formation, no woman has been in the highest leadership position in the organizational structure, namely the general chairperson. The formulation of the problems in the research are: (1) How are the perceptions of the management and members of the FKMB Unesa regarding the absence of women as leaders. (2) What are the inhibiting factors for the election of women as leaders in FKMB Unesa? The theory used in this study is Rosmarie Putnam Tong's Theory of Liberal Feminism. This study uses a descriptive qualitative research method. Data from the study were obtained from interviews with seven administrators and two members, focus group discussions (FGD) with 10 administrators and two members, observation and documentation. The research informants are the management and members of the Unesa FKMB for the 2022/2023 period. In general, informants were of the view that women were not suitable to be general chairmen at FKMB Unesa because women were emotional, women were not destined to be leaders, were hampered by distance and time, were not authoritative, were not suitable as top leaders, and were not flexible as leaders. Meanwhile, women themselves also feel unable to carry out the role of leader. As in the theory of Liberal Feminism, the inhibiting factors for the presence of female leaders are caused by internal and external factors. It can be argued that men and women have different opportunities, women's opportunities to become leaders are not as big as men's opportunities. The absence of women as leaders is caused by two inhibiting factors that reinforce each other, so that women will be further away from opportunities to become leaders. The power of change can occur when both factors want to break down, both men and women can support each other to erode the patriarchal culture that is rooted in the organization. Keywords: Perceptions, Absence of Women Leaders, Inhibitors.